Effect of Pineapple Juice (Ananas comosus) on Surface Roughness of Preheated and Non-Preheated Nanohybrid Composite Resins - Kamadi, Jason; Liliany, Dewi (Indonesian Dental Association, 2022)
Introduction: Nanohybrid composite resins is a type of composite consisting 2 different filler sizes, where one filler ranges in nanoparticles 0.01-0.05µm. Pineapple juice (Ananas comosus) is a widely consumed drink by Indonesian with pH range 3.5-4.6. Surface roughness may be affected by extrinsic factors such as low pH from pineapple juice. Rough surface can cause bacterial adhesion and plaque accumulation on restorative material which cause secondary caries, gingivitis and staining. Preheating is a preparation method of composite which improve composite physical and mechanical properties. Objective: To analyze the difference in surface roughness of preheated and non-preheated nanohybrid composite resins after immersion in pineapple juice. Methods: This research was a laboratory experimental with post-test and control group design. Thirty-three cylindrical sample of nanohybrid composite resin Filtek Z250 XT A2 shade (3M ESPE) (10 mm x 2 mm) were divided into 3 groups: Preheated, Non-preheated and control. Preheated and non-preheated group were immersed in 10 mL pineapple juice for 2 hours for 12 days, control group were immersed in 10 mL distilled water for 24 hours for 12 days. Surface roughness was measured after immersion using surface roughness tester Taylor Hobson, Subtonic S-100 Series-S128) and analyzed using one way ANOVA followed by Post Hoc Tukey. Results: Statistical analyze with one way ANOVA test indicates significant differences between surface roughness in 3 groups with p = 0.034, average surface roughness of pre-heated group was calculated in 0.73 µm, non-preheated group in 0.81 µm and control group in 0.55µm. Tukey’s Post hoc with p = 0.03 shows significant difference in surface of non-preheated composite resin with control group. Conclusion: Pineapple juice increases surface roughness of nanohybrid composite resins after 2 hours immersion for 12 days in comparison with control group.